Perbandingan Rasm Uthmani dan Rasm Imla'i Menurut Perspektif Al-Qawa’id Al-Sittah (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
This paper will discuss how to distinguish mushafs written using the official and rasm ilma'i methods. although the difference between the two ways of writing the manuscripts seems simple, the fact is that many people are still confused about how to determine between the two types of ways of writing the manuscripts. Therefore, the aim of this study is to explain what the Ottoman rasm really is and how to recognize and differentiate between the Ottoman rasm and the Imla'i rasm mushaf. The differences in the two ways of writing manuscripts are collected in Al-Qawa'id Al-Sittah, namely al-hazf, al-ziyadah, al-hamzah, al-badal, al-fasl and al-wasl, as well as sentences that read more than one (ma fihi qiro'atani wakutiba ‘ala ihdahuma. Therefore, this article is an attempt by the reviewer to introduce to the public the importance of understanding the rules for writing the Koran according to Rasm Uthmani and rasm imlai. From the description above it can be concluded that between rasm usmani and rasm imlai have differences and similarities. Rasm usmani has specificities and rules which are sometimes written which necessitate differences with the readings. Even so, in rasm-usmani this difference is not a problem, because the recitation of the Koran is still maintained according to the talaqqi path. While rasm imlai is a treasure of conventional Arabic writing that has developed along with the development of Arabic. Rasm usmani is a history of the writing of the Koran which was copied and narrated from the authors of Usman's mushaf. While rasm imlai is pure ijtihad formulated by language experts, both from the Basrah, Kufa and Baghdad schools of thought. Rasm usmani is only specifically for writing verses of the Qur'an, while rasm imlai applies generally to all non-Qur'anic Arabic texts, including hadith qudsi.